SEED GERMINATION TEST TECHNOLOGY PRACTICUM (STANDARD DEVELOPMENT TEST) - Rika, Mudar; Oktavia, Sri Wina; Fitriani, Riska; Javed, Muhammad Ahmad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
The aim of this practicum is to determine the percentage of seed germination, and to determine the germination capacity of the seed. The tools used in this practicum were a germonator, tweezers, clear plastic, and writing tools and the materials used in this practicum were substrate paper, 25 soybean seeds and 25 corn seeds. The results obtained were: On observations on the first day, it was seen that the germination value of both soybean seeds (Glycine max L) and corn seeds (Zea mays) had not changed because the time needed for the seeds to germinate had not been sufficient. In the 2nd observation, there were changes in soybean seeds (Glycine max L) and in the 3rd observation, there were changes in soybeans (Glycine max L).